EVALUATION OF ON THE JOB TRAINING PROGRAM FOR TEACHERS’ ACADEMIC QUALIFICATION IMPROVEMENT IN CENTRAL KALIMANTAN - Uda, Tonich (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
This research is aimed at conducting evaluation, for providing general description and information for the community at large, regarding the implementation of the On Job Training Program for Teachers’ Academic Qualification Improvement in Palangka Raya City, Central Kalimantan. This program evaluation research was conducted at Teacher Training and Education Faculty of Palangka Raya University, by using qualitative descriptive method, and data collection were carried out through observation, direct interviews, questionnaires and literature studies. The subjects of the research were the teachers who have graduated from On the Job Training Program for Teachers’ Academic Qualification Improvement in Palangka Raya Municipality. The result of the evaluation shows that the implementation of the On the Job Training Program for Teachers’ Academic Qualification Improvement in Palangka Raya City, Central Kalimantan, in general had been well conducted in accordance with the guidelines and regulation which are stipulated in the decree of the Minister of National Education of the Republic of Indonesia, number 58/2008 and number 15/P/2008, the human resources and other resources provided were generally good, the teaching and learning process (lecturing, practical works) has been successfully conducted in accordance with the effective academic guidelines, the program has produced 139 graduates with the fastest study time was 2 semesters and the longest study time was 5 semesters, and the Cumulative Grade Point Average (GPA) is 3.21 for kindergarten and elementary school teachers, 2.90 for Junior High School teachers, and 3.21 for Senior High School teachers, with the graduation predicate of satisfactorily good. The result of the evaluation also shows that in general, the teachers’ competence indicated was fairly good, however, in terms of pedagogical competence; the teachers still need to be improved, especially in competence 2 indicator 1 and in competence 4 indicator 11. Keywords: On the job Training, Teachers’ Academic qualification